IMPLEMENTASI KEBIJAKAN PERCEPATAN PENURUNAN STUNTING OLEH PEMERINTAH KOTA PEKANBARU TAHUN 2021-2022 - Arbi, Fabian; Nasution, Hazqon Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the implementation of Presidential Regulation no. 72 of 2021 concerning the Acceleration of Reducing Stunting in Pekanbaru City in 2021-2022. As a form of implementation of Presidential Regulation no. 72 of 2021, the Pekanbaru City Government issued Pekanbaru Mayor Regulation no. 134 of 2021 concerning the Convergence of Accelerating Prevention and Reducing Stunting. The regulation explains that the Pekanbaru City Government has formed a Special Team to handle the stunting problem in Pekanbaru City, and the name of the team is (TPPS) Stunting Reduction Acceleration Team. The problem of this research is the increasing stunting rate in Pekanbaru City from 11.4% in 2021 to 16.8% in 2022. This research is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques were carried out using interviews and documentation. There are 4 stages of data analysis techniques used, namely data collection, data reduction, data presentation and conclusion drawing. The results of this research indicate that the Implementation of the Policy for Accelerating Stunting Reduction has not been running optimally, there are influencing factors such as the absence of (STRAKOM) strategies that the Pekanbaru City Government has, causing less than optimal socialization which has an impact on the community, many of whom still don't know what it is. stunting, then quite a few people underestimate stunting and the limited funds owned by the Pekanbaru City Government. Keywords: Implementation, Policy, Government, Stunting